2020
DOI: 10.1186/s40985-020-00131-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of being of the female gender for household head on the prevalence of food insecurity in Ethiopia: a systematic-review and meta-analysis

Abstract: Background: Ethiopia signed both for Millennium Development Goals (MDGs) previously and Sustainable Development Goals (SDGs) currently to improve food security through gender equality and empowerment of women by positioning them as household leader. However, there is no concrete evidence about the impact of being of the female gender for household head on the prevalence of food insecurity at the national level, the authors' intention being to fill this gap. Methods: Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 28 publications
6
45
1
2
Order By: Relevance
“…The results of this study also revealed that gender of the household head had a significant association with children's nutritional status only after adjusting for household type, particularly in rural areas. Previous studies in Ethiopia found that female headship increased the likelihood of stunting and underweight among preschoolers (38) and also increased the vulnerability to household food insecurity (39) . In most developing countries, female-headed households are prone to poverty, and they have less access to both job opportunities and government services which then will affect child's outcome (38,40) .…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study also revealed that gender of the household head had a significant association with children's nutritional status only after adjusting for household type, particularly in rural areas. Previous studies in Ethiopia found that female headship increased the likelihood of stunting and underweight among preschoolers (38) and also increased the vulnerability to household food insecurity (39) . In most developing countries, female-headed households are prone to poverty, and they have less access to both job opportunities and government services which then will affect child's outcome (38,40) .…”
Section: Discussionmentioning
confidence: 94%
“…It's been reported the incidence of surgical site infection after cesarean section is relatively high, which ranges from 8.18 [7] to 39.17% [8]. Surgical site infection not only affect the prognosis of pregnant women, but also may involve abdominal organs, and even induce diffuse abdominal infections, thereby prolonging the length of hospitalization, and bringing greater psychological and economic burden to the mothers and their families [9][10][11]. Therefore, it's essential to promptly detect the risk factors of surgical site infection after cesarean section, and to understand the etiological characteristics of surgical site infection after cesarean section.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies [8][9][10][11][12] on female-headed households have focused on cases where women inevitably become head of households in situations of war or in crisis situations in socioeconomically vulnerable countries. However, as South Korea is a member of the Organization for Economic Cooperation and Development (OECD), the vulnerability experienced by female-headed households in Korea means that it is different from these countries.…”
Section: Introductionmentioning
confidence: 99%